Control de inventarios en el Comercial El Favorito, San Juan – Pueblo Viejo, período 2021. - Bravo Pilligua, Tania Maribel (2023)
Inventory control in any company is a fundamental requirement for business finances to have solvency, and in turn coordinate with everything that covers economically within each organization. The commercial "El favorito" has presented problems in its inventories, causing imbalance in its profitability. For this reason, the present case study aims to analyze inventory control in the El Favorito commercial, in San Juan -Pueblo Viejo, in the period 2021. Its research subline was based on financial, tax and social commitment management. As a methodology, it applied a quantitative and qualitative approach, with a retrospective design; The research technique was based on the documentary review of the inventory for the year studied, and an interview addressed to the commercial manager. The results showed that inventory rotation occurs every 360 days, that is, once a year; and in the interview it was evidenced by the aforementioned that the business does not have exact information on the number of products that enter or leave, in addition, a manual inventory is handled that usually presents failures. In conclusion, due to the lack of inventory control, the salesperson can present economic problems that can lead to decision making without considering the risks that it can bring to their profitability and productivity.